1991
DOI: 10.1002/jcla.1860050508
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum lipoprotein(a) concentration with other cardiovascular risk factors in a chinese population

Abstract: The association between serum Lp(a) concentration, a risk factor for atherothrombotic disease, and other cardiovascular risk factors such as smoking, alcohol intake, hypertension, obesity, and indices of glycemic control is examined in a cohort of 313 elderly Chinese subjects (M = 160, mean age +/- SD = 68 +/- 11 year; F = 153, mean age +/- SD = 73 +/- 11). Although associations existed for the above risk factors and other serum lipid levels, there was no association with serum Lp(a) concentration in the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The range of Lp(a) levels for this study population seemed similar to that for the Framingham offspring [7], and significantly lower than that for Japanese and black populations [23,24]. A limited number of studies have reported the median values of Lp(a) for other Chinese ethnic groups, ranging from 7.0 mg/dl for Chinese in Singapore to 25.0 mg/dl for Chinese in Hong Kong [3,12]. However, those measures were based on small sample sizes between 30 and 304.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The range of Lp(a) levels for this study population seemed similar to that for the Framingham offspring [7], and significantly lower than that for Japanese and black populations [23,24]. A limited number of studies have reported the median values of Lp(a) for other Chinese ethnic groups, ranging from 7.0 mg/dl for Chinese in Singapore to 25.0 mg/dl for Chinese in Hong Kong [3,12]. However, those measures were based on small sample sizes between 30 and 304.…”
Section: Discussionsupporting
confidence: 55%
“…However, most studies are hospital-based or employee-based [11] and limited data are available for Asian populations. Only a few studies on Chinese ethnic groups are available and have provided inconsistent data on Lp(a) due to small sample size [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Lp(a) excess accelerates the risk of premature CAD. Numerous studies in several continents within the past decade confirm and extend the previous evidence that Lp(a) is one of the top seven major risk factor for cardiovascular diseases [7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Introductionsupporting
confidence: 53%
“…Lp(a) concentrations were weakly correlated positively with BMI among 186 subjects with 1DDM (13). Furthermore, in several studies, Lp(a) concentrations and BMI or other indexes of upper body obesity were unrelated (41)(42)(43). These conflicting results could be related to the complex interactions between obesity, physical activity, insulinemia, and sex hormone levels.…”
Section: Resultsmentioning
confidence: 97%